Pemilihan Jenis Pohon Potensial Untuk Mendukung Pengembangan Destinasi Wisata Alam di Desa Kamal Kabupatan Seram Bagian Barat - Komul, Yulianus Dominggus (LPPM Univ. Ibn Khaldun Bogor, 2022)
In an effort to optimize forest functions in terms of providing added value to certain regions or villages, especially in the development of nature-based tourism, tree species are selected that have more capabilities than other tree species. This ability can be in the form of carbon dioxide absorption or the ability to absorb other types of pollutant gases that cannot be absorbed by most trees. The selection of tree species can also be done to shape the aesthetics either in urban areas or in areas with special purposes. Types of trees that have a wide canopy, attractive appearance of trees, flower and bear fruit throughout the year, become a place for playing and foraging for birds, originally have values ​​that can be used to shape the aesthetics of the tourist area being built. The main purpose of community service activities is to provide understanding to the community, especially nature tourism business actors, about tree species that are potential and have species suitability when examined from economic, aesthetic and silvicultural values ​​so that they can support the development of natural tourism. The service activity was carried out in Kamal Village, West Kairatu District, West Seram Regency in June 2020. The main focus of community service activities is to provide education to the community and business actors about planting trees and preserving forest as well as introducing potential tree species to help develop Kamal nature tourism. Beach and Pelumena Peak.